Effects of lumbar arthrodesis on adjacent segments: differences between surgical techniques - Kim, Tae Yup; Kang, Kyoung Tak; Yoon, Do Heum; Shin, Hyun Chul; Kim, Keung Nyun; Yi, Seong; Chun, Heoung Jae; Oh, Jae Keun; Choi, Gwi Hyun; Lee, 2nd, Kwang; Ha, Yoon (Spine (Philadelphia, Pa. 1976), 2012)
A finite element analysis. To evaluate the differences between surgical techniques in terms of the effects of arthrodesis on adjacent segments. Augmentation with posterior rigid fixation combined with transpedicular screw insertion, which is one of the most popular techniques for lumbar arthrodesis, shows benefits in immediate stabilization and a higher fusion rate but is reportedly correlated with greater stress on adjacent segments. However, the increased stress on adjacent segments needs further evaluation because the differences of the effects on adjacent segments between surgical techniques, including anterior lumbar interbody fusion, posterior lumbar interbody fusion, and semirigid fixation, have not yet been determined. A finite element model of the human lumbar spine was developed. Three spinal segments (L2-L5) were used to investigate. The intact spinal model was validated by comparing it with previously reported models. Then, 4 arthrodesis models were analyzed and compared: (1) anterior lumbar interbody fusion model; (2) posterior lumbar interbody fusion model; (3) semirigid fixation model combined with posterior lumbar interbody fusion; and (4) rigid fixation model combined with posterior lumbar interbody fusion. Among these 4 models, the rigid fixation model showed the greatest amount of stress, with increased intervertebral disc pressure and contact force of the facet joints of both upper and lower adjacent segments. The second highest stress levels were seen in the semirigid fixation model and the lowest stress levels were seen in the anterior lumbar interbody fusion model. Although bony fusion had been completed, the effects of lumbar arthrodesis on adjacent segments could vary according to the surgical technique used for arthrodesis. Semirigid fixation combined with arthrodesis deserves careful consideration and further detailed study because it may cause less stress on adjacent segments than rigid fixation while maintaining the benefits of the latter procedure.